KOMPOSISI KEBERADAAN KRUSTASEA DI MANGROVE DELTA MAHAKAM KALIMANTAN TIMUR - Pratiwi, Rianta (Makara Journal of Science, 2009)
Crustacean composition on mangrove Mahakam Delta, East Kalimantan. The research was conducted in Mangrove area, Mahakam Delta, East Kalimantan. The aim of this research was to analyze the diversity and the richness of crustacean. The research was done in the locations where dense area (Muara Ilu I), moderate area (Muara Ilu II, P. Tunu) and rare area of mangroves Muara Pantuan (P. Lagenting Luar). The transect research method was used stand upright line of the seashore for mangrove and crustacean. The result of environment parameter shows relative in good condition for living mangrove and crustacean organisms. Total founded crustacean were 40 species and 9 families. The 38 species were non economic values and 2 species were economic values: Varuna yui and Scylla olivacea, also founded 2 new species: Metaplax sp. nov. (Grapsidae) and Macrophthalmus sp. nov. (Sesarmidae). The highest crustacean density varies depend on the environment characteristic of the research station. The highest density was 1456 ind/m2 (station 6) and the lowest density was 27 ind/m2 (station 8). Diversity Index was lower category (H’ = 3.0700), while Similarity Index (E = 2.0180) was high enough, so the distribution of crustacean relatively similar. Dominancy Index was low (C = 1.6270). While the highest mangrove diversity Index was at Muara Ilu I (H = 2.14) and following by Muara Ilu II (H = 1.40) and Mauara Pantuan (H = 2.03). Over all the three locations of mangrove vegetation (tree, belta and seed) are in the lower categories diversity index, similarity index and dominance index.